SOSIALISASI PENDAMPINGAN ANAK DI ERA DIGITAL UNTUK WALI MURID DI TAMAN PENDIDIKAN AL QUR’AN NURUL IKHSAN - Ika Romadoni Yunita; Chyntia Raras Ajeng Widiawati; Aulia Shafira Tri Damayanti; Luthfi Khaerunnisa (Nusantara Hasana Journal, 2023)
During the Covid-19 pandemic, the use of information technology such as gadgets in children seemed unavoidable. Because almost all school learning is carried out online, this makes children more attached to their gadgets or devices. In the We Are Social report it is known that internet users have several different electronic devices, such as mobile phones, smartphones and non-smartphones, laptops/PCs, tablets, smartwatches, and so on. Of these various types of devices, mobile phones are the most popular devices. The problem is that not all parents understand today's digital era children, as well as the proper rules for using digital media. This was felt by the parents or guardians of TPQ Nurul Ikhsan students in Sokawera Village, Somagede District. So it is necessary to assist children when using their gadgets so that they can be used wisely. Participants in this socialization activity were 22 parents/guardians of students, previously 77% of whom still did not understand children's character and the rules for using digital media. The results of this activity after the participants received the socialization material were as many as 63% of the parents/guardians of the students who attended became participants who understood the children's character and the rules for using digital media after receiving the socialization material. In addition, 23% of participants understood enough and the percentage of participants who did not understand decreased to 14%.